COMPARATIVE ANALYSIS OF THE COMPONENT COMPOSITION OF PROFESSIONAL CULTURE OF FUTURE SPECIALISTS - Oksana Pilevich (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
It has been elucidated in the article that the appearance of new types of culture is natural result of complication and differentiation of human activity, emergence of new professions. Every professional group of people produces a special system of ethical principles that define the style of interaction with clients, colleagues, management, external agencies, etc. the author proves that educational institutions and professional associations follow these principles and styles, save them, make a system of knowledge, skills, practical experience and rules of conduct, lay them in the professional culture. The structure of professional culture of future specialists of different professions is analyzed. Methodological basis for the definition of its components is studied.